Russia Protest Against U.S. Plans to Place Military Equipment in Eastern Europe Countries in 2015 - Krisnadi, Muhammad Faiz (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
After the fall of the Soviet Union thereafter the Cold War, the rivalry between the United States and Russia remains prevalent. This paper seeks to find why Russia is protesting the U.S. plan to pace military equipment in Eastern Europe. The Eastern European Region is located in the eastern part of the European continent, consisting of post-Soviet Union countries. These countries are often associated with the term "Eastern Bloc" during the Cold War. Using power transition theory, the author will be explaining the nature of war concerning power in international relations. Additionally, power transition theory shows that hegemony's increasing power and rivalry tends to be difficult to resolve by peaceful means. In compiling this research, the author used the descriptive qualitative method. The form of the method used is Literature Review or library research. After collecting the data, the writer will analyze using explanatory research and take a conclusion. The study found that in the wake of the Ukraine conflict and Russian hostility towards NATO, the United States has proven to be the most committed and capable ally of the Central and Eastern European (CEE) states as the controlling power in the region.